The first case report of human infection with Phyllobacterium myrsinacearum causing spondylodiscitis. (October 2020) - Hughes, Gareth; Pollard, Christopher; Chavda, Swarupsinh; David, Miruna D.
Abstract: Phyllobacterium myrsinacearum is an organism not previously described as causing infections in humans. We report the case of a 63-year-old gentleman who presented with breathlessness, reduced Glasgow Coma Scale and septic shock requiring intensive care unit admission. Whilst CT imaging showed a severe pneumonia, it also revealed findings consistent with an L1–2 discitis. The biopsy of this spinal disc revealed the above organism on 16S rDNA Real-Time PCR. Having initially thought this may be a contaminant, extensive step-wise review of the processing of the sample suggested this was likely to be a true finding and left us with a number of questions such as how did it get there, what was the optimal antibiotic regimen and how long to treat it for? Highlights: A tissue/bone biopsy is critical in the diagnosis and treatment of discitis/vertebral osteomyelitis particularly when blood cultures are sterile If the biopsy is negative on standard culture it should be sent to a reference laboratory for a 16S rDNA Real-Time PCR Improved diagnostic tools in Microbiology are providing an increased spectrum of organisms from patient samples – going through a logical stepwise approach can help the clinician decide on the relevance of these organisms To the best of our knowledge this is the first human case of Phyllobacterium myrsinacearum causing spondylodiscitis infection.